Analysis of caesarean delivery using Robson ten group classification system at a tertiary care teaching institute in Kerala, India - T., Heera Shenoy; Shenoy, Sheela T.; T., Anaswara; K., Remash (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Globally, the caesarean delivery rate is rising continuously, making caesarean one of the most common surgical procedures. The Robson classification, appreciated by WHO in 2014 and FIGO in 2016 is widely accepted, risk-based, ten-group classification system (TGCS) developed specifically to assess caesarean section rates. The aim of this study was to know the rate of Caesarean section in present hospital, to analyse the Caesarean sections based on Robson’s classification and to determine the contribution and significance of each group on the overall number of Caesarean sections. Methods: All women, who gave birth by Caesarean deliveries done over a period of 1 year (January 2018-December 2018) in Travancore Medical College Hospital in South Kerala India. Results: Group 5 (previous LSCS, single, cephalic >37 weeks) made the greatest contribution to the Caesarean section rate (27.24%). The second highest contributor was Group 2 (Nulliparous, singleton, cephalic, >37 weeks induced labour or caesarean section before labour followed by Group 10 (all single cephalic <36 weeks including previous CS) 18.78%. Conclusions: Limiting the CS rate in low-risk pregnancies is key to lowering the trend of increased CS. If TGCS is used uniformly, CS rates can be compared over time and between units, both nationally and internationally.